2013
DOI: 10.1117/12.2035999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the DICOM grayscale standard display function on the accuracy of medical-grade grayscale and consumer-grade color displays for telemammography screening

Abstract: The aim of this study was to compare the diagnostic accuracy of consumer-grade and medical-grade monitors with very different costs for breast cancer detection when used with and without the Digital Imaging and Communication in Medicine (DICOM) standard calibration. This study was retrospective, with a factorial design and repeated measures, and used 70 digital mammograms (40 benign or normal cases and 30 malignant cases), four radiologists, and three displays with and without display calibration. Film mammogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…These findings indicate that the digital devices provided comparable diagnostic accuracy to the reference treatment (FILM). In addition, these results are in agreement with our previous evaluation of displays (also including a medical-grade grayscale display) using images obtained with CR [17], as well as the evaluation of capture devices (including standard CR) visualized using a medical-grade grayscale display. Previous studies have compared film-screen mammography to digitized films [9][10][11], and similar to the present study, these reports found no significant differences in diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These findings indicate that the digital devices provided comparable diagnostic accuracy to the reference treatment (FILM). In addition, these results are in agreement with our previous evaluation of displays (also including a medical-grade grayscale display) using images obtained with CR [17], as well as the evaluation of capture devices (including standard CR) visualized using a medical-grade grayscale display. Previous studies have compared film-screen mammography to digitized films [9][10][11], and similar to the present study, these reports found no significant differences in diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 90%
“…The study of Krupinski [30] found also comparable result between medical-grade displays and consumer-grade displays, with more appreciated differences in the evaluation of subtle lesions, especially when the monitors have been used more than a year. In addition, in part of the our overall study when images from CR were included and all the images were reading using a medical-grade display, in addition to the consumer-grade displays of this evaluation, no differences were observed in detection of nodules and calcifications in screening mammograms when GSDF calibration or factory calibration was used [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations